ENVIRONMENTAL SERVICES AND ECOSYSTEM SERVICES: CONCEPTUAL DIFFERENCE AND APPLICATION IN BRAZILIAN ENVIRONMENTAL LEGISLATION - Folharini, Saulo de Oliveira; de Oliveira, Regina Célia (Geoambiente On-line, 2020)
The concept of Ecosystem Services proposed in the 1970s gained wider discussion in the 1990s, mainly due to the increased engagement of member countries of the United Nations in building policies for sustainable dksevelopment that consider human needs and the preservation of natural resources, drawing to this end on efforts from various fields of science. Different sectors of academia, such as biology and geography, contributed to this interdisciplinary discussion with studies in the environmental area and other fields of science that do not effectively work with concepts like ecosystem and environment, and sometimes use these concepts incorrectly in their works to explain a given phenomenon. In order to contribute to the interdisciplinary discussion related to Ecosystem Services and Environmental Services, this article proposes a review of the concepts of ecosystem and environment, including the Payment for Services model, whether environmental or ecosystem, and of Brazilian federal legislation on the subject, contributing to the discussion on how these terms can be used in a more feasible way to address phenomena studied in different kinds of research.